2015
DOI: 10.7314/apjcp.2015.16.1.321
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metabolic and Anatomic Response to Chemotherapy Based on PERCIST and RECIST in Patients with Advanced Stage Non-small Cell Lung Cancer

Abstract: Background: The aim of this study was to explore the prognostic role of metabolic response to chemotherapy, determined by FDG-PET, in patients with metastatic non-small-cell lung cancer (NSCLC). Materials and Methods: Thirty patients with metastatic NSCLC were analyzed for prognostic factors related to overall survival (OS) and progression free survival (PFS). Disease evaluation was conducted with FDG-PET/CT and contrast-enhanced CT prior to and at the end of first-line chemotherapy. Response evaluation of 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…So far, however, there only relatively few and mostly small studies comparing RECIST and PERCIST (References: [17] [42] [43] [44] [45] [46] [47] [48] [20] [49] [50] [51] [21] [52] [53] [24] [23] [25] [54] [26] [55] [56]). A meta-analysis published in 2016 identified 6 studies including 268 patients [57].…”
Section: Limitations Of Recist and Opportunities For Fdg Pet Based Rementioning
confidence: 99%
“…So far, however, there only relatively few and mostly small studies comparing RECIST and PERCIST (References: [17] [42] [43] [44] [45] [46] [47] [48] [20] [49] [50] [51] [21] [52] [53] [24] [23] [25] [54] [26] [55] [56]). A meta-analysis published in 2016 identified 6 studies including 268 patients [57].…”
Section: Limitations Of Recist and Opportunities For Fdg Pet Based Rementioning
confidence: 99%
“…Therefore, FDG uptake may be useful in the differentiation of tumor tissue, fibrosis and necrosis for which anatomical boundaries are not always distinguishable. Ordu et al (14) reported in their study that, in advanced NSCLC patients, in evaluation of response to chemotheraphy and in determination of overall survival, the metabolic response with PERCIST may be an early predictive factor in comparison with morphologic response. Our study showed that although there was no significant change in the longest total dimension, the change in post-treatment SUVmax was significant whether only the longest dimension of the primary tumor or of target lesions were taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Specificity remains low, confounded by tumour associated inflammation, while sensitivity for tumour deposits smaller than the 0.5 cm is lacking because of limited spatial resolution (especially problematic in NSCLC mediastinal nodal assessment) [10]. Repeatability coefficients of 18 FDG-PET SUVmean and SUVmax, which have been extensively studied for use in treatment response evaluation [32,34,35], are in the range 25e50% [36e39]. This is improved by measuring the SUV of the 30 most avid voxels rather than SUVmax or SUVpeak [40].…”
Section: Metabolic Markersmentioning
confidence: 99%